Determinan Yang Mempengaruhi Perilaku Pembelian Produk Hijau Di Daerah Istimewa Yogyakarta - Mathori, Muhammad; Chasanah, Uswatun (JURNAL RISET MANAJEMEN SEKOLAH TINGGI ILMU EKONOMI WIDYA WIWAHA PROGRAM MAGISTER MANAJEMEN, 2019)
This study aims to identify the determinants that influence the attitudes of consumers of green purchases and the willingness to pay more on green products, specifically on energy-saving lighting products. The variables studied included environmental knowledge, environmental awareness and perceived effectiveness. The sample of this study was 196 students, but out of 196 respondents after the questionnaire was distributed only 189 could be processed. Validity and reliability test results show valid values of loading factors of more than 0.4 while for reliability testing using the cronbach’s alpha criteria above 0.5 indicates reliable. Through the multiple linear regression analysis, the variables of environmental knowledge, environmental awareness and effectiveness are felt to have a positive and significant effect on the attitude of buying and willingness to pay more. Green purchasing attitudes and willingness to pay more have a positive and significant effect on green purchasing behavior. Green purchasing attitudes have a greater influence on green purchasing behavior compared to willingness to pay more.